(untitled) (Bangladesh Journal of Plant Taxonomy, 2011)
Not available Keywords: Cyanobacteria; Diversity; Nitrogen-fixing; Rice fields; North Bihar. DOI: 10.3329/bjpt.v18i1.7842 Bangladesh J. Plant Taxon. 18(1): 73-76, 2011 (June)